Bilateral thoracic Paravertebral block for immediate postoperative pain relief in the PACU: a prospective, observational study - Fei Liu; HuanKai Zhang; Yunxia Zuo (BMC Anesthesiology, 2017)
Abstract Background To investigate the feasibility, effectiveness and safety of bilateral thoracic paravertebral block (TPVB) in the post anesthesia care unit (PACU) for pain relief in participants after laparotomy. Methods A single shot of bilateral TPVB with 25 ml of 0.2% ropivacaine and 5 mg dexamethasone in combination for both sides at the 8th thoracic transverse level (T8) was performed on 201 participants who complained moderate to severe pain on arrival to PACU after laparotomy. The visual analog scale (VAS) pain scores at rest and on cough, heart rate, blood pressure, and pulse oximetry before and after bilateral TPVB for up to 1 h were recorded. The VAS Pain scores at rest and on cough at 24 h after bilateral TPVB were also recorded. Results Bilateral TPVB was carried out successfully in all participants. The VAS pain scores at rest and on cough were 7.9 ± 1.6 and 8.7 ± 1.3 respectively pre-bilateral TPVB. The VAS pain scores at rest and on cough were significantly decreased to 1.1 ± 1.2 and 2.1 ± 1.6 respectively (P < 0.001) at 60 min after bilateral TPVB and to 2.1 ± 1.7 and 3.8 ± 1.9 at rest and on cough respectively ((P < 0.001) at 24 h after bilateral TPVB. At 10 min post-bilateral TPVB, only systolic blood pressure was reduced from 122 ± 19 mmHg to 111 ± 18 mmHg (P = 0.007) but then gradually became stable. No complications related to bilateral TPVB were observed. Conclusion Bilateral TPVB can be provided for pain relief to the participants who suffer from moderate to severe pain after upper laparotomy in the PACU. Trial registration Chinese Clinical Trial Registry: ChiCTR-ONN-16009229 , Registered on 10 September 2016.